Steroidal and Nonsteroidal Mineralocorticoid Receptor Antagonists Cause Differential Cardiac Gene Expression in Pressure Overload-induced Cardiac Hypertrophy. Issue 5 (May 2016) - Grune, Jana; Benz, Verena; Brix, Sarah; Salatzki, Janek; Blumrich, Annelie; Höft, Beata; Klopfleisch, Robert; Foryst-Ludwig, Anna; Kolkhof, Peter; Kintscher, Ulrich
Abstract : Abstract: Pharmacological blockade of mineralocorticoid receptors (MR) is known as an efficacious therapy in chronic heart failure. Therapy with steroidal MR antagonists such as spironolactone or eplerenone (EPL) is often limited because of side effects. Recently, a new highly selective and potent, nonsteroidal MR antagonist, finerenone (FIN), has been developed. To investigate the effects of FIN on pressure-induced cardiac hypertrophy, the transverse aortic constriction (TAC) model was used in C57BL/6 mice treated with FIN (10 mg·kg −1 ·d −1 ), EPL (200 mg·kg −1 ·d −1 ) or vehicle (VEH). First, we analyzed cardiac gene expression 4 weeks after TAC using a pathway-focused quantitative polymerase chain reaction array. FIN caused a distinct cardiac gene expression profile compared to VEH and EPL, including differential expression of BNP (brain natriuretic peptide) and Tnnt2 (troponin T type 2). FIN treatment led to a significant reduction of TAC-induced left ventricular (LV) wall thickening assessed by echocardiography. In accordance, FIN-treated mice showed a significant lower increase of calculated left ventricular mass compared with VEH- and EPL-treated mice (FIN: 28.4 ± 3.7 mg; EPL: 38.4 ± 4.3 mg; VEH: 39.3 ± 3.1 mg; P < 0.05). These data show beneficial effects of nonsteroidal MR antagonism by FIN on left ventricular mass development in pressure overload associated with a distinct cardiac gene expression profile. Abstract : Supplemental Digital Content is Available in the Text.